Adaptive Leadership in Islamic Primary Schools: Navigating Digital Transformation and Twenty-First Century Disruption - Yusuf; Nida Nurjunaedah (BASICA, 2026)
The rapid advancement of digital transformation has posed significant challenges for Islamic primary schools (Madrasah Ibtidaiyah), requiring school leaders to improve educational quality while preserving Islamic values and institutional identity. These challenges extend beyond technology adoption to include organizational adaptation, leadership capacity, and sustainable school development. This study aims to analyze the strategic role of adaptive leadership in enabling principals to navigate digital transformation and respond effectively to the educational demands of the twenty-first century. The study employed a qualitative library research approach by systematically reviewing peer-reviewed journal articles, academic books, policy documents, and other authoritative publications related to adaptive leadership, digital transformation, and Islamic education. The findings reveal that adaptive leadership strengthens organizational adaptability through collaborative decision-making, continuous professional learning, digital literacy development, innovation-oriented school management, and value-based governance grounded in Islamic principles. Furthermore, adaptive school leaders are better positioned to foster institutional resilience by integrating technological innovation with stakeholder collaboration and sustainable organizational learning. This study concludes that adaptive leadership provides a comprehensive strategic framework for guiding digital transformation in Islamic primary schools while maintaining their Islamic educational identity. The findings contribute to the development of adaptive leadership literature by offering an integrated conceptual perspective that combines organizational adaptation, digital transformation, and Islamic educational values within the context of Madrasah Ibtidaiyah.